Manipulating self and other schemas to explore psychological processes associated with paranoid beliefs: an online experimental study - Martinez, Anton P.; Milne, Elizabeth; Rowse, Georgina; Bentall, Richard P. (Frontiers in Psychology, 2025)
BackgroundInformation about the self and others is organized in cognitive-affective structures that influence and guide interpersonal behavior. These structures are referred to as relational schemas and are thought to be influenced by early interpersonal experiences with significant others leading to secure or insecure attachment patterns as adults. When insecure, these patterns appear to contribute to paranoid interpretations about the intentions of others by indirect pathways such as negative self-esteem and a bias toward untrustworthiness. Experimental studies employing classical conditioning (CC) interventions have been successful in manipulating these schemas, finding significant effects on various psychological outcomes such as attachment styles, implicit self-esteem, and paranoid beliefs. However, no study to date has explored these effects on trustworthiness judgments.ObjectiveThis study aims to replicate the findings from previous experiments and also testing the effect of manipulating relational schemas on trustworthiness evaluations.MethodsA convenience online sample of 266 participants completed a series of tasks and questionnaires measuring attachment styles, explicit and implicit self-esteem, paranoia, and trustworthiness evaluations before and after a brief CC intervention, which involved being randomly allocated to three conditions. In each of these conditions, information about the self was always paired with either positive face stimuli (proximity-seeking condition), negative face stimuli (self-threat condition), or neutral face stimuli (control condition).ResultsThis study failed to replicate findings as previously reported in published experiments (i.e., self-esteem, paranoia), only finding a significant effect on attachment styles on the proximity-seeking CC condition. Moreover, no effect was found regarding trustworthiness judgments.DiscussionLimitations such as the online nature of the study and methodological aspects are discussed.